The unheard melodies : a study of Japanese Noh and Samuel Beckett’s waiting for godot - Pang, Jeannette Ru Yan (2017)
This paper is about Japanese Noh and Beckett's Waiting for Godot. It sets up a transcultural analysis of the aesthetics resonances across the works from two different cultures.